Mixed Reality in Modern Surgical and Interventional Practice: Narrative Review of the Literature - Mats T Vervoorn; Maaike Wulfse; Tristan P C Van Doormaal; Jelle P Ruurda; Niels P Van der Kaaij; Linda M De Heer (JMIR Publications, 2023)
BackgroundMixed reality (MR) and its potential applications have gained increasing interest within the medical community over the recent years. The ability to integrate virtual objects into a real-world environment within a single video-see-through display is a topic that sparks imagination. Given these characteristics, MR could facilitate preoperative and preinterventional planning, provide intraoperative and intrainterventional guidance, and aid in education and training, thereby improving the skills and merits of surgeons and residents alike. ObjectiveIn this narrative review, we provide a broad overview of the different applications of MR within the entire spectrum of surgical and interventional practice and elucidate on potential future directions. MethodsA targeted literature search within the PubMed, Embase, and Cochrane databases was performed regarding the application of MR within surgical and interventional practice. Studies were included if they met the criteria for technological readiness level 5, and as such, had to be validated in a relevant environment. ResultsA total of 57 studies were included and divided into studies regarding preoperative and interventional planning, intraoperative and interventional guidance, as well as training and education. ConclusionsThe overall experience with MR is positive. The main benefits of MR seem to be related to improved efficiency. Limitations primarily seem to be related to constraints associated with head-mounted display. Future directions should be aimed at improving head-mounted display technology as well as incorporation of MR within surgical microscopes, robots, and design of trials to prove superiority.